The scope and application of similar fact evidence under the Evidence Act 1950: introduction and its overview from the perspective of Islamic law of evidence - Mazupi Abdul Rahman,; Ahmad ‘Azam Mohd Shariff, (Fakulti Undang - Undang, 2003)

(untitled)
The Principle of Similar Fact Evidence has been well outlined in Section 11(b), Section 14 and Section 15 of the Malaysian Evidence Act 1950. Its scope and application by the Malaysian Courts have always come under close scrutiny and comments as the Malaysian Judiciary often adopts a critical and analytical approach when deciding on the question of admissibility of such evidence. This short article however aims at giving a very brief and basic introduction to the scope and application of similar fact evidence as applied by the Malaysian courts in the simplest possible manner. At the same time, since the principle is relatively new to the Syariah, this article also strives at briefly analyzing the principle of similar fact evidence in the eyes of Islamic Law of Evidence and suggesting for its applicability and admissibility in the Syariah courts if such evidence is to be tendered by any party in a Syariah criminal or civil trial. It is humbly hoped that this writing could, in the future, provoke a more detailed and juristic study on the admissibility of evidence of a similar fact in the eyes of Islamic Law of Evidence and Islamic Judiciary